Governando indivíduos e populações: as faces do biopoder nas páginas da revista Veja (1979 – 1988) - Silva, André Luís Andrade (2024)
This thesis problematizes the journalistic statements of Veja magazine, using as a research source a set of cover stories from editions published between 1979 and 1988, whose purpose is to govern the lives of individuals and the population. The selected cover stories were separated into three groups: (1) those that seek to manage the body of individuals; (2) those whose purpose is to manage the subjects interiority; and (3) those that convey knowledge and security alerts with the aim of managing the lives of the population. Veja magazine cover stories are examined through the methodological framework of Michel Foucault archaeogenealogy, based on the principle that the periodical is a device of biopower, that is, a network made up of multiple discourses that establish and circulate knowledge, exercising power over the lives of individuals and the population as a positive, productive and transformative force, stimulating individuals and organizes the social status of the population. The general objective of this work is to investigate the conditions of possibility for the emergence of these journalistic statements that seek to exercise power over the lives of individuals and the population, as well as the effects of this discursive production. To solve our problem, we structured the work into three fronts of investigation, which are developed in three chapters. In the first chapter, the objective is to understand how Veja journalistic statements seek to manage individuals bodies. In this sense, the practice of sports, physical exercises and aesthetic procedures that seek to build and/or maintain bodily beauty emerge on the pages of Veja as human capital whose purpose is to optimize bodies so that they become more efficient at work, produce flows income and achieve success. The second chapter deals with cover stories that focus on managing the interiority of individuals, that is, that indicate how they should behave, feel, act and make decisions in their lives. Therefore, acquiring new knowledge and cognitive skills, managing your emotions, being autonomous and seeking happiness and constant selfesteem become important human capital, a competitive advantage that can put individuals ahead of others. In the third chapter, the cover stories that aim to manage the lives of the population as a species are investigated, through the dissemination of medical and scientific knowledge that promotes health, as well as journalistic statements that convey statistical data, issue standards, controls, regulations and warnings about population safety. In short, the investigation in Veja consists of denaturalizing the look at this vehicle of communication, allowing us to identify the knowledge and forces that span the years 1979 to 1988 and, at the same time, question some of our contemporary certainties regarding the type of subject we have become.